(3eNJGQGJ TYQjIs - (3GdHhQjfj , GdMSf Hf eMeO Hf eMeO Hf MSf GdUahQj GdHhQjfj, HOQ GdOjf,J (B1024 (3g` s
(3ChdgG (B:s
(3hbGd (B((3GdeJfHj(B) (3jhOY CHG TLGY YVOGdOhdI aOi dc ef ojbUQ Yf eOGcG adG edc EPkG EdG aOGcG s
(3BNQgG (B:s
(3GdPd Ydi LaGc Yjf GdpYR hGdVjYI aj MeGc Yjf GdMQR bHdJ JQGH efRd CfJ Hg jG aQMI NGWQj fHjd GdcfR s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3Gdbde GdfSN eVHhW CMjGfkG hHgG NWhW CNQis
(3cKjQ ef gPg GdeNJGQGJ dHOQGdOjf GdMSf GdUahQj GdHhQjfjs
(3ef TYQgs
(3Ch GNJGQgs
(3HNWg s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs